Early and Accurate Identification of Parkinson Disease Among US Veterans - Mantri, Sneha (Fed Pract, 2019)
Early and accurate identification and management of veterans at risk for Parkinson disease is an important priority area for the US Department of Veterans Affairs because of the substantial impact on quality of life and disability-adjusted life years.